Epidemiological study of congenital heart defects in children and adolescents: analysis of 4,538 cases - Miyague,Nelson Itiro (2003)
OBJECTIVE: To analyze the frequency and prevalence of congenital heart defects in a tertiary care center for children with heart diseases. METHODS: We carried out an epidemiological assessment of the first medical visit of 4,538 children in a pediatric hospital from January 1995 to December 1997. All patients with congenital heart defects had their diagnoses confirmed at least on echocardiography. The frequency and prevalence of the anomalies were computed according to the classification of sequential analysis. Age, weight, and sex were compared between the groups of healthy individuals and those with congenital heart defects after distribution according to the age group. RESULTS: Of all the children assessed, 2,017 (44.4%) were diagnosed with congenital heart disease, 201 (4.4%) with acquired heart disease, 52 (1.2%) with arrhythmias, and 2,268 (50%) were healthy children. Congenital heart diseases predominated in neonates and infants, corresponding to 71.5% of the cases. Weight and age were significantly lower in children with congenital heart defects. Ventricular septal defect was the most frequent acyanotic anomaly, and tetralogy of Fallot was the most frequent cyanotic anomaly. CONCLUSION: Children with congenital heart defects are mainly referred during the neonatal period and infancy with impairment in gaining weight. Ventricular septal defect is the most frequent heart defect.